The feasibility of psychometric measures for body image and lymphedema for routine practice. Issue 1 (13th January 2020) - Hollyhead, Cyan; Branney, Peter
Abstract: The aim of this study is to assess the feasibility of the Male Genital Self‐Image Scale (MGSIS‐5) and Groin and Lower Limb Lymphedema questionnaire (G3L‐20) in a community sample of cisgender men aged 40 years and older. Psychometric measures can aid urologic practice by prompting patients to talk about aspects of their body that are either too sensitive or a natural part of aging. Importantly, reliable and valid measures can also contribute to an evidenced‐based‐practice‐based‐evidence cycle where they can establish the impact of changes recommended by research while using the results in turn to inform research. In this study, we examine two psychometric measures on the opposite ends of a psychological‐physical continuum; the MGSIS‐5 and the G3L‐20. A non‐experimental psychometric design was employed, administering the questionnaires online to a community sample of cisgender men aged 40 years old and above. Validity and reliability analyses were conducted. Thirty men completed the study; 14 aged 40 to 49, 14 aged 50 to 59 and 2 aged 60 to 69. The MGSIS‐5 and G3L‐20 show acceptable reliability and validity with one‐ and three‐component structures, respectively. The MGSIS‐5 and G3L‐20 show sufficient feasibility to justify the resources for studies with larger community samples and for pilot studies with clinical populations.